Public Service Innovation on Stunting Overcoming in North Luwu Regency - Idrus, Iqbal Aidar; Syah, Syahiruddin (Jurnal Manajemen Pelayanan Publik, 2024)
The dispute of stunting tends to be a severe public health problem in Indonesia, including in North Luwu Regency. Stunting has a long-term impact on children's physical growth, cognitive development, and health. Furthermore, it has the potential to cause lasting health and social problems. Therefore, this research proposes to explore and evaluate public service innovations that have helped overcome stunting in North Luwu Regency. This research implies a qualitative method with a documentation approach and data analysis using Nvivo 12 Plus software, as well as validation through data triangulation from various sources to ensure the accuracy and trustworthiness of the findings. The findings of this study show that North Luwu Regency, through the "Kejar Stunting" Program, has significantly reduced stunting rates through stakeholder commitment, cross-sector collaboration, and a focus on prevention. With solid support from various related parties, this program reduces the prevalence of stunting and has a real positive impact on the welfare of children and families in the region. The "Kejar Stunting" program has been proven to significantly reduce stunting rates in North Luwu Regency through a comprehensive and collaborative approach. This emphasizes the importance of public service innovation in dealing with serious public health problems.